2012
DOI: 10.1364/oe.20.024218
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum generation in tapered chalcogenide fiber for producing octave-spanning frequency comb around 3 μm

Abstract: Abstract:We demonstrate mid-infrared (mid-IR) supercontinuum generation (SCG) with instantaneous bandwidth from 2.2 to 5 μm at 40 dB below the peak, covering the wavelength range desirable for molecular spectroscopy and numerous other applications. The SCG occurs in a tapered As 2 S 3 fiber prepared by in-situ tapering and is pumped by femtosecond pulses from the subharmonic of a mode-locked Er-doped fiber laser. Interference with a narrow linewidth c.w. laser verifies that the coherence properties of the near… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 29 publications
1
78
0
2
Order By: Relevance
“…Chalcogenide glasses are interesting candidates, combining as they do nonlinear refractive indices that are ~200 times greater than fused silica, high refractive indices and a transparency window that can extend out beyond λ = 10 µm. A number of different waveguide structures based on chalcogenide glasses have been reported in literature, including step-index fibers [18,19], fiber tapers [20,21] and microstructured fibers [22]. In this paper we report efficient mid-IR SC-generation at extremely low pump pulse energies (< 20 pJ) in a hybrid step-index waveguide consisting of a cylindrical chalcogenide core embedded in a silica fiber capillary ( Fig.…”
Section: Introductionmentioning
confidence: 81%
“…Chalcogenide glasses are interesting candidates, combining as they do nonlinear refractive indices that are ~200 times greater than fused silica, high refractive indices and a transparency window that can extend out beyond λ = 10 µm. A number of different waveguide structures based on chalcogenide glasses have been reported in literature, including step-index fibers [18,19], fiber tapers [20,21] and microstructured fibers [22]. In this paper we report efficient mid-IR SC-generation at extremely low pump pulse energies (< 20 pJ) in a hybrid step-index waveguide consisting of a cylindrical chalcogenide core embedded in a silica fiber capillary ( Fig.…”
Section: Introductionmentioning
confidence: 81%
“…In recent years, several experimental and theoretical investigations on mid-infrared SC generation were reported in ChG planar waveguides [13][14][15], ChG fibers [16][17][18][19][20][21][22][23][24][25][26][27][28], single crystal sapphire fibers [29], silicon-on-insulator (SOI) wire waveguides [30], ZBLAN fiber [31], fluoride glass [32] and germano-silicate fibers [33]. Gai et al [13] reported SC generation from 2.9 µm to 4.2 µm in dispersion-engineered As 2 S 3 glass rib waveguide (6.6 cm long) pumped with 7.5 ps duration pulses at a wavelength of 3.26 µm with a pulse peak power of around 2 kW.…”
Section: Introductionmentioning
confidence: 99%
“…Mφ ller et al [28] used a 18 cm long, low-loss, suspended core As 38 S 62 fiber and generated a SC spanning from 1.7 to 7.5 µm by pumping this fiber with 320 fs pulses with a peak power of 5.2 kW at a wavelength of 4.4 µm. The SC generation in As 2 S 3 fibers and waveguides has been limited to 5 µm due to their increased losses in the long wavelength region [13,17,18]. Although As 2 Se 3 chalcogenide glass has its loss edge in the long wavelength region around 16-17 µm, the use of such materials for SC generation has so far been limited owing to high peak power pump sources required in the MIR region [4,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Shifting zero-dispersion wavelength closer to the emission line of Cr:ZnS laser will be very important for obtaining the octave-spanning supercontinuum using quite simple femtosecond Cr:ZnS oscillator as a pump source. That could be done by optimizing the core diameter or tapering the fiber 13 .…”
Section: Wavelength (Nm)mentioning
confidence: 99%